Experimentation and the Returns to Entrepreneurship - Manso, Gustavo (Review of Financial Studies, 2016)
Previous studies have argued that entrepreneurs earn less and bear more risk than salaried workers with otherwise similar characteristics. In a simple model of entrepreneurship, I show that estimates of mean and variance of returns to entrepreneurship used by these previous studies are biased, as they fail to account for the option value of experimenting with new ideas. Using longitudinal data, I find patterns that are consistent with entrepreneurship as experimentation and returns to entrepreneurship that are more attractive than established by previous research.